Weissbuch Gastroenterologie 2020/2021 Erkrankungen des Magen-Darm-Traktes, der Leber und der Bauchspeicheldrüse - Gegenwart und Zukunft - Lammert, Frank; Lynen Jansen, Petra; Lerch, Markus M. (De Gruyter, 2019)
After cardiovascular illnesses, non-malignant diseases of the digestive tract are the most common illnesses affecting Germans, resulting in around 2 million hospitalizations every year. With the updated White Paper, the German Society for Digestive and Metabolic Diseases (DGVS) offers a validated scientific and statistical foundation to underpin the discussion of the present and future status of gastrointestinal diseases in Germany.